Desizing of untreated cotton fabric with the conventional and ultrasonic bath procedures by immobilized and native alpha-amylase - YILMAZ, BURCU; KAHRAMAN, MEMET VEZİR (WILEY-BLACKWELL, 2011)
In this work, starch-sized, untreated 100% cotton plain woven fabric was treated with native and immobilized a-amylase enzyme in two different system (conventional and ultrasonic bath procedures) and time (15 and 30 min). Weight loss, the amount of removed starch, tensile properties, contact angle, and scanning electron micrograph morphology were investigated. Sonification and treatment time enhance the desizing performance. Free enzyme, treatment time, and ultrasound brings about a significant increase in the starch-size removal along with a decrease in the retained strength values, regardless of the used fabric. Immobilized enzyme can be use many times which enables to improve environment friendly pretreatment processes for the textile industry.
Keywords: Cotton fabric; Desizing; Electron microscopy; Enzyme; Tensile strength; BIO-PREPARATION; ENERGY